Biological concepts in human sodium channel epilepsies and their relevance in clinical practice. (23rd February 2020) - Brunklaus, Andreas; Du, Juanjiangmeng; Steckler, Felix; Ghanty, Ismael I.; Johannesen, Katrine M.; Fenger, Christina Dühring; Schorge, Stephanie; Baez‐Nieto, David; Wang, Hao‐Ran; Allen, Andrew; Pan, Jen Q.; Lerche, Holger; et al.
Abstract: Objective: Voltage‐gated sodium channels (SCNs) share similar amino acid sequence, structure, and function. Genetic variants in the four human brain‐expressed SCN genes SCN1A/2A/3A/8A have been associated with heterogeneous epilepsy phenotypes and neurodevelopmental disorders. To better understand the biology of seizure susceptibility in SCN ‐related epilepsies, our aim was to determine similarities and differences between sodium channel disorders, allowing us to develop a broader perspective on precision treatment than on an individual gene level alone. Methods: We analyzed genotype‐phenotype correlations in large SCN ‐patient cohorts and applied variant constraint analysis to identify severe sodium channel disease. We examined temporal patterns of human SCN expression and correlated functional data from in vitro studies with clinical phenotypes across different sodium channel disorders. Results: Comparing 865 epilepsy patients (504 SCN1A, 140 SCN2A, 171 SCN8A, four SCN3A, 46 copy number variation [CNV] cases) and analysis of 114 functional studies allowed us to identify common patterns of presentation. All four epilepsy‐associated SCN genes demonstrated significant constraint in both protein truncating and missense variation when compared to other SCN genes. We observed that age at seizure onset is related to SCN gene expression over time. Individuals with gain‐of‐function SCN2A/3A/8A missense variants or CNV duplications share similar characteristics, most frequently present with early onset epilepsy (<3 months), and demonstrate good response to sodium channel blockers (SCBs). Direct comparison of corresponding SCN variants across different SCN subtypes illustrates that the functional effects of variants in corresponding channel locations are similar; however, their clinical manifestation differs, depending on their role in different types of neurons in which they are expressed. Significance: Variant function and location within one channel can serve as a surrogate for variant effects across related sodium channels. Taking a broader view on precision treatment suggests that in those patients with a suspected underlying genetic epilepsy presenting with neonatal or early onset seizures (<3 months), SCBs should be considered.